Eficiência nutricional , aminoácidos na planta e proteína de grão de genótipos de cevada - Klein, Catia Beatris (2018)
Brewing industries are increasingly demanding barley genotypes with higher nitrogen nutritional efficiency and protein content to produce special malts. However, this efficiency is in general low and varies with environmental and genetic factors. The objective of this work was to evaluate the nutritional efficiency of nitrogen, plant amino acid content, and grain protein content of barley genotypes grown in soils fertilized with two nitrogen rates. Plants of 18 barley genotypes—9 cultivars (ABI-Balster, ABI-Voyager, ANA-2, ANAG-01, Andrea, BRS-Brau, BRS-Cauê, BRSKorbel, and Grace) and 9 lineages (A, B, C, D, E, F, G, Merit-57, and MN-6021)—were grown in soils fertilized with 30 or 95 mg kg-1 of nitrogen. The experiment was conducted in a two way completely randomized block design, by testing 2 N rates × 18 barley genotypes, with two replications. The experimental unit were pots with 7.7 kg of soil and barley plants. The plants were grown in growth chambers, under temperature of 20±2 ºC, photoperiod of 12 hours, and photosynthetically active radiation of 500 μmol/m 2 /s. The interaction between genotypes and nitrogen rates had significant effect on grain weight and protein content, and amino acids in the xylem and phloem of the spike. The BRS-Brau, Cauê, and Korbel cultivars, and the F and G lineages were the most efficient genotypes in grain production, in both nitrogen rates. The highest correlations between grain dry weight and nutritional efficiency type were found for nitrogen use and absorption efficiency, in both rates of this nutrient. The correlations between these types of efficiency and grain protein content were significant only with the highest nitrogen rate, but the correlation was negative for nitrogen use efficiency, and positive for absorption efficiency. The nitrogen distribution in the stem had the highest relative contribution to determine the genetic variability among the genotypes. The nutritional efficiency of nitrogen, amino acid content in the phloem and xylem of the spike, and grain protein content of the barley plants present variability due to the genotypes and soil nitrogen fertilization rates.